French University Libraries 1988-1998: A Statistical Analysis - Gabel, Gernot U. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Based on an analysis of statistical data from the past decade which have been published annually by the French Ministry of Education (Annuaire des bibliothèques universitaires), the article gives an overview of developments with regard to buildings, personnel, services, acquisitions and collections of French university libraries during the last decade.